2008
DOI: 10.1080/17450390801892583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a probioticLactobacillus acidophilusstrain on feed tolerance in dogs with non-specific dietary sensitivity

Abstract: This study investigated the effects of the probiotic Lactobacillus acidophilus strain DSM 13241 in dogs with non-specific dietary sensitivity (NSS). Six adult German Shorthair Pointers with NSS consecutively received a control dry diet and the same diet supplemented with the probiotic (6 x 10(6) cfu/g) for 12 weeks each, followed by another control period of four weeks. Frequency of defecations, faecal quality and nutrient digestibility were determined. Faeces were cultured for Clostridium perfringens, Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Despite the fact that probiotic products are becoming increasingly used in small animal practice, there are few published studies regarding their clinical effect. Although there are some studies concerning the clinical efficacy of probiotic lactobacilli in chronic enteropathies (Sauter and others 2006, Pascher and others 2008), their effect in acute diarrhoeas has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that probiotic products are becoming increasingly used in small animal practice, there are few published studies regarding their clinical effect. Although there are some studies concerning the clinical efficacy of probiotic lactobacilli in chronic enteropathies (Sauter and others 2006, Pascher and others 2008), their effect in acute diarrhoeas has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Digestive tolerance reflects the reaction of the animal to the diet, although different authors may have used different terms such as gastrointestinal tolerance (Knapp et al, 2008) or nonspecific dietary sensitivity (Pascher et al, 2008). Digestive tolerance can be assessed by determining fecal quality (consistency, moisture, volume, odor, and color), and several studies have shown that there is a wide range of digestive tolerance levels among dogs, especially related to body size, breed, or both (Meyer et al, 1999;Weber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics may control enteric colonization by pathogens through different mechanisms, such as interference, reduction or exclusion of bacterial adhesion and also production of substances that inhibit pathogen growth (Reid 1999). In addition, probiotic administration in dogs may have a role in the therapy of other intestinal disorders like inflammatory bowel disease, diarrhea and constipation by different causes or enteric cancer (Pascher et al 2008;Chrzastowska et al 2009) and even may be useful to prevent urogenital infections (Delucchi et al 2008).…”
Section: Introductionmentioning
confidence: 98%